2005
DOI: 10.1128/jcm.43.4.1937-1939.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 in Illicit-Drug Solutions Used Intravenously Retains Infectivity

Abstract: The stability of the human immunodeficiency virus type 1 (HIV-1) strain IIIB in drug solutions was studied. The data demonstrate that HIV-1 infectivity can be retained in drug solutions (e.g. , heroin, “Khanka,” and “Vint”) for long periods of time. This fact must be taken into account when designing health education programs for the prevention of HIV and AIDS in Eastern Europe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Since METH potentiates FIV replication in vitro [52], we sought to determine the effects of METH on the replication of a CXCR4-tropic virus (HIV-1 IIIB) in IDC. HIV-1 IIIB has been shown to remain infectious for several days in METH solutions [53]. The current study demonstrates that pretreatment of IDC with METH prior to infection with HIV-1 IIIB (X4) enhances viral replication.…”
Section: Discussionmentioning
confidence: 69%
“…Since METH potentiates FIV replication in vitro [52], we sought to determine the effects of METH on the replication of a CXCR4-tropic virus (HIV-1 IIIB) in IDC. HIV-1 IIIB has been shown to remain infectious for several days in METH solutions [53]. The current study demonstrates that pretreatment of IDC with METH prior to infection with HIV-1 IIIB (X4) enhances viral replication.…”
Section: Discussionmentioning
confidence: 69%
“…A study by Nair’s group (Reynolds et al 2006) found that heroin potentiates HIV replication in human astrocytes. Using human T lymphoid cell line, Selimova et al demonstrated that heroin increased HIV replication at the early stages of its life cycle (Bobkov et al 2005; Selimova et al 2002). …”
Section: Opiates and Hivmentioning
confidence: 99%
“…41,42 While we did not find an association between PFSU and HIV or HCV infection, PFSU could increase the likelihood of BBV infection if the syringe is not sterile or the drugs are drawn from a common container that becomes infected. 12 Further, others report that prefilled syringes are often shared. 16 Thus, it is important that education messages address PFSU as well as related high-risk behaviors for HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…PFSU may have influenced HIV transmission among PWIDs in some Eastern European countries (e.g., Russia and Ukraine); however, drug preparation methods and time between preparation and distribution of prefilled syringes influences their infectivity and potential for the spread of disease. [9][10][11][12] There is a dearth of information about this practice from the USA.…”
Section: Introductionmentioning
confidence: 99%